2017
DOI: 10.2174/1381612823666170707165319
|View full text |Cite
|
Sign up to set email alerts
|

Circadian MicroRNAs in Cardioprotection

Abstract: The most dramatic feature of life on Earth is our adaptation to the cycle of day and night. Throughout evolutionary time, almost all living organisms developed a molecular clock linked to the light-dark cycles of the sun. In present time, we know that this molecular clock is crucial to maintain metabolic and physiological homeostasis. Indeed, a dysregulated molecular clockwork is a major contributing factor to many metabolic diseases. In fact, the time of onset of acute myocardial infarction exhibits a circadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 98 publications
(131 reference statements)
0
32
0
Order By: Relevance
“…miR-21, a highly expressed miRNA in the heart, has a crucial function of modulating normal biological processes of the myocardial tissue (40). Accumulating evidence also suggests that the miR-21/PTEN pathway exhibits critical actions on cell survival and death in the cardiovascular system (24,41,42).…”
Section: Discussionmentioning
confidence: 99%
“…miR-21, a highly expressed miRNA in the heart, has a crucial function of modulating normal biological processes of the myocardial tissue (40). Accumulating evidence also suggests that the miR-21/PTEN pathway exhibits critical actions on cell survival and death in the cardiovascular system (24,41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it exhibits the potential to act as a useful therapeutic target. Numerous studies have been conducted researching the pathogenesis of CVD ( 18 ). Furthermore, miRNA alterations have been demonstrated to be involved in angiogenesis, myocardial hypertrophy, heart failure and myocardial fibrosis ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been conducted researching the pathogenesis of CVD ( 18 ). Furthermore, miRNA alterations have been demonstrated to be involved in angiogenesis, myocardial hypertrophy, heart failure and myocardial fibrosis ( 18 ). The present study demonstrated that the downregulation of miRNA-145 increased cardiac cell apoptosis in an in vitr model of AMI.…”
Section: Discussionmentioning
confidence: 99%
“…miR-21 expression is endogenously high in cardiomyocytes, vascular endothelial cells, cardiac fibroblasts and vascular smooth muscle cells (17). Although, the physiological functions of miR-21 in cardiovascular diseases have not been fully determined, the contribution of miR-21 in various cardiovascular diseases, including heart failure, myocardial infarction, myocardial fibrosis and atherosclerosis are being uncovered (18)(19)(20). Studies have shown that miR-21 is involved in numerous pathophysiological processes associated with myocardial I/R injury (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%